Molecular Components of the Neurospora crassa pH Signaling Pathway and Their Regulation by pH and the PAC-3 Transcription Factor. - Stela Virgilio (PLoS ONE, 2016)
Environmental pH induces a stress response triggering a signaling pathway whose components have been identified and characterized in several fungi. Neurospora crassa shares all six components of the Aspergillus nidulans pH signaling pathway, and we investigate here their regulation during an alkaline pH stress response. We show that the N. crassa pal mutant strains, with the exception of Δpal-9, which is the A. nidulans palI homolog, exhibit low conidiation and are unable to grow at alkaline pH. Moreover, they accumulate the pigment melanin, most likely via regulation of the tyrosinase gene by the pH signaling components. The PAC-3 transcription factor binds to the tyrosinase promoter and negatively regulates its gene expression. PAC-3 also binds to all pal gene promoters, regulating their expression at normal growth pH and/or alkaline pH, which indicates a feedback regulation of PAC-3 in the pal gene expression. In addition, PAC-3 binds to the pac-3 promoter only at alkaline pH, most likely influencing the pac-3 expression at this pH suggesting that the activation of PAC-3 in N. crassa results from proteolytic processing and gene expression regulation by the pH signaling components. In N. crassa, PAC-3 is proteolytically processed in a single cleavage step predominately at alkaline pH; however, low levels of the processed protein can be observed at normal growth pH. We also demonstrate that PAC-3 preferentially localizes in the nucleus at alkaline pH stress and that the translocation may require the N. crassa importin-α since the PAC-3 nuclear localization signal (NLS) has a strong in vitro affinity with importin-α. The data presented here show that the pH signaling pathway in N. crassa shares all the components with the A. nidulans and S. cerevisiae pathways; however, it exhibits some properties not previously described in either organism.